Cluster headache and middle meningeal artery dural arteriovenous fistulas: A case report. (October 2018) - Chang, Yu-Han; Luo, Chao-Bao; Wang, Shuu-Jiun; Chen, Shih-Pin
Background: Of the multiple etiologies identified for symptomatic cluster headache, vascular origin is common; however, there are no known reports of arteriovenous (AV) fistulas. Here we report a case with typical presentation of cluster headache, which might be associated with middle meningeal AV fistulas. Case report: The subject is a 49-year-old man with a 7-year history of episodic left-side cluster headache, consistent with the criteria in the International Classification of Headache Disorders, 3rd edition, beta version (ICHD-3β). Magnetic resonance angiography (MRA) demonstrated dural arteriovenous fistulas at the left posterior fossa, which is supplied mainly by the left middle meningeal artery. After endovascular balloon-assisted embolization, his symptoms have disappeared without relapse for 1.5 years. Discussion: We suggest that middle meningeal arteriovenous fistulas should be considered as a potential differential diagnosis of secondary cluster headache, even when the initial clinical manifestations and treatment response are typical for primary cluster headache.